Effect of Developmental Care on the Duration of Mechanical Ventilation in Preterm Infants - S Sabaghi; M Nourian; M Fallahi; M Nasiri (Iran University of Medical Sciences, 2016)
Abstract Background & Aims: Respiratory diseases are the common cause of hospitalization of preterm infants in neonatal intensive care unit. Although mechanical ventilation has saved many infants' lives, like other treatments; it has not been without harm. Developmental care intervention is a potential method for reducing the duration of mechanical ventilation in infants. The aim of this study was to determine the effect of developmental care interventions on duration of mechanical ventilation in preterm infants with respiratory distress syndrome. Material & Methods: This quasi-experimental non-randomized study was conducted on 60 preterm infants of gestational age ≤33 weeks with respiratory distress syndrome who were divided into intervention and control groups. Infants in the control group received routine nursing care, and those in the intervention group received developmental care as well as routine care. Results: Mean duration of ventilation was 3.63±2.94 days in control group and 4.06±3.05 days in intervention group, with no significant difference between the two groups (P=0.57). Conclusions: According to the results obtained, developmental care interventions had no effect on duration of mechanical ventilation in preterm infants with respiratory distress syndrome.